Gene Expression Analysis of HPRT-Deficient Cells Maintained with Physiological Levels of Folic Acid - Rosa J. Torres; Gerard Valentines-Casas; Claudia Cano-Estrada; Neus Ontiveros; José M. López (Cells)
Lesch–Nyhan disease (LND) is associated with a complete deficiency of hypoxanthine-guanine phosphoribosyltransferase (HPRT) activity due to mutations in the HPRT1 gene. Although the physiopathology of LND-related neurological manifestations remains unknown, a defective neuronal developmental process is the most widely accepted hypothesis. We generated an HPRT-deficient line from the pluripotent human embryonic cell line NT2/D1 by CRISPR-Cas9 and induced its differentiation along neuroectodermal lineages by retinoic acid treatment. As levels of folic acid in the culture media may affect results in LND models, we employed physiological levels of folate. The effect of HPRT deficiency on neural development-related gene expression was evaluated using two methodological approaches: a directed qPCR array of genes related to neuronal differentiation, and global gene expression by RNAseq. HPRT-deficient pluripotent cells presented altered expression of genes related to pluripotency in human embryonic stem cells, such as DPPA3 and CFAP95, along with genes of the homeobox gene family. HPRT-deficient pluripotent cells were able to differentiate along neuro-ectodermal lineages but presented consistent dysregulation of several genes from the homeobox gene family, including EN1 and LMX1A. GO enrichment analysis of up- and downregulated genes in HPRT-deficient cells showed that the most significant biological processes affected are related to development and nervous system development.